2000
DOI: 10.1128/jvi.74.15.7032-7038.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Virus-Specific and Allospecific Cytotoxic T-Lymphocyte Response to Lymphocytic Choriomeningitis Virus Is Modified in a Subpopulation of CD8+T Cells Coexpressing the Inhibitory Major Histocompatibility Complex Class I Receptor Ly49G2

Abstract: The role of negatively signaling NK cell receptors of the Ly49 family on the specificity of the acute CD8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Whether infection leads to up-regulation of Ly49 family members is not as clear-cut. Only ϳ2% of lymphocytic choriomeningitis virus (LCMV) 3 -specific CD8 ϩ T cells in infected mice express Ly49G2 (15), which is similar to the percentage of Ly49G2 ϩ CD8 ϩ T cells in uninfected mice. However, a significantly larger population of Ly49 ϩ CD8 ϩ T cells was reported in mice infected with influenza virus (12).…”
mentioning
confidence: 81%
“…Whether infection leads to up-regulation of Ly49 family members is not as clear-cut. Only ϳ2% of lymphocytic choriomeningitis virus (LCMV) 3 -specific CD8 ϩ T cells in infected mice express Ly49G2 (15), which is similar to the percentage of Ly49G2 ϩ CD8 ϩ T cells in uninfected mice. However, a significantly larger population of Ly49 ϩ CD8 ϩ T cells was reported in mice infected with influenza virus (12).…”
mentioning
confidence: 81%
“…Previous studies showed that LCMV-and influenza-specific CD8 ϩ T cell populations express Ly49A or Ly49G2 NK receptors, respectively (2,36). To determine whether LCMV-specific CD8 ϩ T cells express Ly49 receptors, we stained splenocytes with mAbs specific for Ly49 A, D, F, G2, I/C, and I receptor isoforms at multiple time points following acute LCMV infection.…”
Section: Resultsmentioning
confidence: 99%
“…It might be expected that KLRG1 expression would be lower on Ag-specific cells in the acute, compared with the latent stage. Indeed, there is some evidence that other NK cell inhibitory receptors are not expressed by a large fraction of activated effector CD8 ϩ T cells during acute primary infection with EBV or hepatitis B in humans (20) or lymphocytic choriomeningitis virus in mice (21). It is interesting to add that a recent report has identified preserved or increased expression of inhibitory receptors on NK cells of HIV-infected viremic individuals, in contrast to activating receptors, which were down-regulated in these patients (22).…”
Section: Discussionmentioning
confidence: 99%